High-dose rate brachytherapy in the treatment of cancer of the cervix uteri - D. A. Aliyev; I. G. Isayev; K. S. Akperov; E. G. Guliyev (Опухоли женской репродуктивной системы)
Analysis of the results of examining and treating 246 patients with Stages IIA-IIIB cancer of the cervix uteri (CCU), receiving specific chemoradiotherapy (CRT) at the Department of Radiotherapy, National Oncology Center (Baku), has ascertained that CRT using two high-dose (9 Gy) rate brachytherapy fractions and competitive cisplatin chemotherapy is an effective, reasonably safe, and economically sound treatment method for locally advanced CCU. The method shows acceptable toxicity and may be used in routine clinical practice.